2013
DOI: 10.2527/jas.2012-5660
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hair fatty acid profile, reproduction, and milk performance in Holstein Friesian cows

Abstract: The aim of this study was to analyze the relationship between the fatty acid profiles of hair of first parity cows and their reproduction and milk performance. Hair samples from 46 German Holstein cows, 50 to 62 d postpartum, were analyzed to assess the relationship. All cows were fed the same diet. The lipid composition of hair was determined by gas chromatography. The fat content in the hair was 0.86%. Hair lipids contributed 75.14% SFA, 15.81% MUFA, and 9.92% PUFA. Cows were classified into a high and a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…Thus, a hair sample reflects the metabolism of the last 1–3 weeks . In a previous study, we found a relationship between hair fatty acids, reproduction, and milk protein production and suggested C12:0 as a useful biomarker to assess energy utilization . Furthermore, an additional study confirmed that C12:0 is related to energy intake and energy utilization in early lactating cows .…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Thus, a hair sample reflects the metabolism of the last 1–3 weeks . In a previous study, we found a relationship between hair fatty acids, reproduction, and milk protein production and suggested C12:0 as a useful biomarker to assess energy utilization . Furthermore, an additional study confirmed that C12:0 is related to energy intake and energy utilization in early lactating cows .…”
Section: Introductionmentioning
confidence: 57%
“…Existing Extraction Method : The existing extraction method is a modified Folch method that has been described previously . In brief, total lipids of 150 mg mill‐ground hair were extracted using 8 mL chloroform/methanol (2:1, v/v).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations